IMPLEMENTATION OF LEGAL PROTECTION FOR VICTIMS OF HUMAN TRAFFICKING AT THE DENPASAR DISTRICT PROSECUTOR'S OFFICE - Ngakan Nyoman Krisna Payadnya; Ni Made Jaya Senastri; Ni Made Puspasutari Ujianti (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
Legal protection for victims is a state obligation to guarantee human rights, especially for victims of human trafficking who experience physical, psy-chological, and social suffering. The Denpasar District Attorney's Office has a strategic role in providing legal protection to victims of human trafficking during the law enforcement process. This study examines the forms of legal protection for victims of human trafficking at the Denpasar District Attor-ney's Office and examines how legal protection is implemented for victims of human trafficking at the Denpasar District Attorney's Office. The research method used is empirical legal research with a statutory, conceptual, and so-ciological approach. That the form of legal protection includes identity pro-tection, assistance, examination in a special room, and fulfillment of restitu-tion rights. Its implementation is carried out through a victim-perspective approach and coordination with relevant agencies. Legal protection has been implemented, but still needs strengthening. That it can be directed at opti-mizing coordination and fulfilling victims' rights on an ongoing basis.